2022
DOI: 10.1007/s12640-022-00599-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subchronic Aluminum Exposure on Learning, Memory, and Neurotrophic Factors in Rats

Abstract: Aluminum (Al) is a neurotoxin that gradually accumulates in the brain in human life, resulting in oxidative brain injury related to Alzheimer's disease (AD) and other diseases. In this study, the learning and memory of rats exposed to different aluminum concentrations ( 0.0 g/L, 2.0 g/L, 4.0 g/L and 8.0 g/L) were studied, and the learning and memory of rats were observed by shuttle box experiment. With HE staining, Western Blot, Immuno uorescence, and RT-PCR, the morphology of nerve cells in the hippocampus of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…That is primarily because AD is a multifactorial disorder with complex pathophysiology which is far from complete elucidation 12 . Several studies demonstrated that neurodegenerative alterations identified in the brain with elevated aluminum level were similar to those observed in AD 13–16 and that aluminum can speed up Aβ aggregation and induce neurofibrillary tangles formation in the brain 17,18 . Thus, aluminum‐induced AD model can be used for investigating the pathogenesis and novel therapeutics for AD 18,19 …”
Section: Introductionmentioning
confidence: 97%
“…That is primarily because AD is a multifactorial disorder with complex pathophysiology which is far from complete elucidation 12 . Several studies demonstrated that neurodegenerative alterations identified in the brain with elevated aluminum level were similar to those observed in AD 13–16 and that aluminum can speed up Aβ aggregation and induce neurofibrillary tangles formation in the brain 17,18 . Thus, aluminum‐induced AD model can be used for investigating the pathogenesis and novel therapeutics for AD 18,19 …”
Section: Introductionmentioning
confidence: 97%
“…Aluminium is the third (after O and Si) most abundant metal in the Earth's crust, at ~8.3%. Because of its abundant reserves, excellent stability, strong conductivity, and low density, it has been applied extensively in many fields such as construction, automobile manufacturing, food processing, and medical and health care [1, 2]. Widespread human activities have led to the release of free aluminium ions (Al 3+ ) into the ecological environment.…”
Section: Introductionmentioning
confidence: 99%